IQ differences of identical twins reared apart are significantly influenced by educational differences - Jared C. Horvath; Katie Fabricant (Acta Psychologica)
Over the last century, several large studies have been published exploring IQ differences amongst monozygotic (MZ) twins reared apart (TRA). By and large, this work has reported that MZ TRAs differ in IQ by ~8.0 points and demonstrate and intraclass correlation (ICC) of ~0.75. Unfortunately, this prior research has largely been amalgamated: it averages data from dozens of TRA pairs without accounting for important life experiences, including education (which has demonstrated a causal impact on IQ performance). In this paper, we gathered data from every available TRA case published in the academic literature over the last century that included both individualized IQ and biographical data. This data set (which we believe represents the entirety of the non-amalgamated TRA field) consists of 87 pairs. For our analysis, we split these pairs into three groups: similar, somewhat dissimilar, and very dissimilar schooling. Analyses reveals that schooling differences have a significant impact not only on the absolute IQ difference between TRA pairs (5.8, 12.1, and 15.1 points, respectively), but also the ICC (0.87, 0.80, 0.56, respectively). These findings raise an important question regarding the historic use of ICC as a measure of genetic influence on IQ and other psychological traits. It is recommended the field of TRA studies focus on individual pairs instead of groups and that researchers share individualized data from TRA pairs included in historic aggregate analyses.